Implementation of Blended Learning Model in Pancasila Education Courses in Education University of Indonesia - Rina Patriana Chairiyani; Dasim Budimansyah; Kama Abdul Hakam; Yadi Ruyadi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Blended learning is a learning method that combines direct learning (synchronous) with indirect or independent learning that can be done at anytime (asynchronous). This research aims to determine the implementation of the blended learning model in Pancasila education courses at the Indonesian University of Education. This research was conducted at the Indonesian University of Education involving 60 students. Data collection was carried out using interviews. Data analysis used qualitative descriptive analysis. The result showed that the learning process using the blended learning model basically has five important keys that must be considered in its implementation, namely 1) live events, 2) independent learning with online materials, 3) collaboration, 4) assessment, 5) performance support materials. These results showed that students are helped by blended learning, both via Zoom and YouTube. Keywords: Blended learning, Direct Learning, Pancasila Education Course